Improving the competitiveness of the Serbian economy through education reforms - Jevtović, Jelena (Industrija, 2023)
Our research analyses how the current reforms in the field of education could affect the competitiveness of the economy of the Republic of Serbia and what kind of reforms are necessary in this field in order to achieve sustainable growth and economic development. The analysis presents how the competitiveness of a country can be measured, covers questions on whether is education one of the indicators of competitiveness, evaluates competitiveness of the Serbian economy, reviews current state in all the relevant indicators in the field of education and considers all relevant reforms.By using the Global Competitiveness Index and one of its pillars dealing with human capital, specifically indicators of Pillar 6 – Skills, we have shown that the quality of the human capital is one of the basic factors of competitiveness and that only quality education can lead to the rapid development of the economy and enhance greater competitiveness of a country. We have concluded that there is a great necessity in the Republic of Serbia for further reforms and investments in the education, especially in education of teaching staff and an innovative teaching programmes and curriculum for the most dynamic economy sectors, like ICT, trade, transport, tourism and financial services.
Keywords: competitiveness, economic development, reforms, economic governance, education